“More than the travels around the world, on your nest full of peace, you find each time the playful love:” Lollobrigida’s motherhood in admirers’ letters - Federico Vitella (Cinergie)
Post-World War II fan letters were more a means to something than an end for their writers. And yet it was certainly not excluded that the fans of this or that actor were content to compliment the career of their favorites or to generically wish for their serenity, without expecting anything in return. Many letters were stimulated precisely by the anniversary of major holidays, by the release of a new film, by a birthday, if not by even more specific personal contingencies, such as Gina Lollobrigida’s pregnancy, the subject of unparalleled media coverage in 1957 Italy. The Biblioteca Chiarini (Centro Sperimentale di Cinematografia) still preserves a small sample of the bursting flow of letters of congratulations that accompanied the publication of this or that update article on Milko Junior’s gestation, including simple expressions of good wishes, reflections on parenthood, tributes materials (blankets and dresses) and even a lullaby specially composed to help the child sleep and guarantee the right rest for the exceptional mother. The present article intends to study this extraordinary corpus of letters, problematizing the historiographical evidence acquired from studies on letters to the powerful.